Systematic Literature Review: Penggunaan Energi Regeneratif dari Sistem Pengereman pada Kereta Listrik/Electric Multiple Unit (EMU) - Mutaqqin, Mutaqqin; Prawira, Dimas Adi; Darmawan, Arief; Marsusiadi, Edi Nyoto Setyo (Innovative: Journal Of Social Science Research, 2024)
One way to reduce energy consumption in electric trains is by using regenerative braking methods. This article aims to present a literature review on the utilization of regenerative braking energy in Electric Multiple Unit (EMU). A descriptive study with a qualitative literature review approach was conducted. The utilization of regenerative braking energy in Electric Multiple Unit (EMU). A total of 10 studies conducted between 2019-2023 were included in this review, out of a total of 1,788 identified titles. These 10 studies met the criteria discussing the utilization of regenerative braking energy in Electric Multiple Unit (EMU) trains. The function of Energy Storage Systems (ESS) or devices as large-capacity energy storage which generates regenerative braking in trains through batteries, flywheels, supercapacitors, and is distributed directly from one train to another to enhance the utilization of electric energy from regenerative braking, including scheduling regulation, reversible substations, and ESS installation, thus capable of saving energy by up to 30%.